2018
DOI: 10.1149/2.1391809jes
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Anode-Supported Solid Oxide Fuel Cells under Load Trip and Cycle Conditions and Their Degradation Prevention Operating Logic

Abstract: To design durable and reliable solid oxide fuel cells (SOFCs) for commercialization, we investigate the degradation behavior of yttria-stabilized zirconia-based anode-supported cells under two electrical load conditions -load trip (0.2-0 A • cm −2 ) and load cycle (0.20-0.12 A • cm −2 ) modes for 60 times (about 1,450 h). During the load trip condition, the operating voltage of the cell decreases by 86 mV through the 1,443 h operation (60 load trips) with the degradation ratio of 9.1% (59.5 μV • h −1 at 0.2 A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…During normal SOFC operations, water is produced by the electrochemical reactions of transported oxygen ions through the electrolyte with hydrogen in the NiO-YSZ fuel electrode. Kim et al reported that atmospheres with a high water content (high a H 2 O ) that are formed in the anode during hydrogen oxidation reactions result in the growth and oxidation of Ni particles that become NiO in the fuel electrodes. This is because the increased a H 2 O in the gas phase leads to increased Ni­(OH) 2 in the anode .…”
Section: Resultsmentioning
confidence: 99%
“…During normal SOFC operations, water is produced by the electrochemical reactions of transported oxygen ions through the electrolyte with hydrogen in the NiO-YSZ fuel electrode. Kim et al reported that atmospheres with a high water content (high a H 2 O ) that are formed in the anode during hydrogen oxidation reactions result in the growth and oxidation of Ni particles that become NiO in the fuel electrodes. This is because the increased a H 2 O in the gas phase leads to increased Ni­(OH) 2 in the anode .…”
Section: Resultsmentioning
confidence: 99%
“…These BFCs consist of bioelectrodes where glucose, the substrate, undergoes the process of oxidation at the anode by the catalytic activity of an enzyme and subsequently produces electrons, which are responsible for creating electricity. Several factors affect the cell output efficiency, namely-the concentration of fuel, the mode or mechanism of transfer of electrons, the action of the enzyme, the potential of the cell, and others [ 21 , 79 , 80 ].
Fig.
…”
Section: Types and Preparation Of Biofuel Cellsmentioning
confidence: 99%
“…To match the fluctuating electricity demand and generation in a future electricity grid, dominated by renewable energy sources like wind and photovoltaic, dynamic operation of fuel cells is required. Previous research has shown that the degradation und therefore the lifespan of Solid Oxide Cell (SOC) stacks shows a significant dependency on the operating conditions and dynamic load changes [3]. However, some research suggests that the degradation is not caused by the load changes itself but spatial temperature gradients during load changes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%